AKUNTABILITAS BELANJA DAERAH DI PEMERINTAH KABUPATEN LUWU UTARA - Dandi Darmadi; Hamsina; Muhammad Rusdi; Nur Indrayati Nur Indar (Journal Publicuho, 2022)
The purpose of this study is to analyze and find the supporting and inhibiting factors of regional financial accountability and specifically regarding regional expenditures for the North Luwu district government. The method used in this study is a qualitative descriptive type with data collection techniques including primary data and secondary data. The results of the study which were analyzed based on the four elements of accountability according to Jonathan Koppel showed that the Transparency Dimension still had weaknesses in terms of timeliness in budget preparation and access to public information. Dimensions of Liability, where the consequences of misuse of the budget for employees who are not actively working are required to be returned in the amount of Rp. 91,848,019. In the Control Dimension, the Internal Inspectorate Supervisor is still not optimal, such as the low value of the follow-up to the findings of the BPK-RI that has been completed, while the DPRD supervision is quite good. Meanwhile, the responsibility dimension is still lacking because there is an expenditure budget that is used in vain and does not bring outcomes, such as equity participation in PDAM Luwu Utara. The last dimension is responsiveness, which can be seen from 1464 proposals for musrenbang only 606 proposals are accommodated. In addition, there are also supporting and inhibiting factors in the accountability of North Luwu Expenditures.